NTB Tourism Image Recovery Strategy After the Earthquake - Syiam, Nazilatus (Communicatus: Jurnal Ilmu komunikasi, 2022)
This study aims to find out how to restore the tourism image of the West Nusa Tenggara (NTB) area after the 2018 natural disaster through the NTB Bangkit Recovery program implemented by the Tourism Office. The paradigm used in this research is constructivism and an interpretive approach using case study research methods. Researchers want to understand how to restore the image of NTB tourism destinations to restore the number of tourist visits. Data collection techniques by conducting observations and in-depth interviews. The results showed that the strategy of restoring the image of the post-earthquake tourism destinations in NTB was carried out: First, identifying opinions. Second public awareness. Third, identify the issue. Fourth, evaluation with the category of assessment of pre-implementation and evaluation of post-implementation of the Recovery NTB Bangkit program. Â 